Starting with the geodesic equation with non-relativistic approximation:(adsbygoogle = window.adsbygoogle || []).push({});

[tex] \frac{d^2 x^{\mu}}{d \tau^2} + \Gamma_{00}^{\mu} \left( \frac{dx^0}{d\tau} \right)^2 = 0 [/tex]

I know that ## \Gamma_{\alpha \beta}^{\mu} = \frac{\partial x^{\mu}}{\partial y^{\lambda}} \frac{\partial^2 y^{\lambda}}{\partial x^{\alpha} \partial x^{\beta}}##, so

[tex]\Gamma_{00}^{\mu} = \frac{\partial x^{\mu}}{\partial y^{\lambda}} \frac{\partial^2 y^{\lambda}}{\partial t^2} [/tex]

How did they get the relation ##\Gamma_{00}^{\mu} = -\frac{1}{2} g^{\mu \lambda} \frac{\partial g_{00}}{\partial x^{\lambda}}##?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Quick question on Geodesic Equation

Loading...

Similar Threads for Quick question Geodesic |
---|

I Question about time and space |

I Relativistic addition question |

B Theoretical Question On The Twins Paradox and Heart Rate |

I Some geometry questions re Schwarzschild metric |

I Derivation of geodesic equation from the action - quick question |

**Physics Forums | Science Articles, Homework Help, Discussion**